PYROLYSIS OF CORN COB BIOMASS TOWARD GASEOUS PRODUCTS ON SMALL CAPACITY REACTOR - Yuliansyah, Fisal; Hamidi, Nurkholis; Sasongko, Mega Nur (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2024)
Corn waste is the result of agricultural production that can be further utilized and get additional economic for the community. Waste Corn cab is one of Indonesia abundant biomass apart from. The utilization of biomass by implementing pyrolysis process can be viable solution. This study aims to observe the determination corn cab pyrolysis using HCL-bentonite activation and without bentonite towards syngas product (CH4-H2-CO-CO2). Updraft reactor was utilized for 30 minutes pyrolysis process. We used MQ4, MQ8, MQ7 coupled with Arduino UNO for measuring CH4, H2, CO2 and CO in ppm unit. Compared without bentonite, the result showed that methane (CH4) gas production increased. In addition, we found also that hydrogen (H2) gas increased respectively. Not mention, the content of CO increased.